Global Asias: Method, Architecture, Praxis - Chen, Tina (The Journal of Asian studies, 2021)
This essay draws on the philosophy, principles, and practices animating Global Asias scholarship to consider how this conceptual rubric shifts the ways in which we approach the subjects, objects, methods, and praxes of the academic study of Asia. Structurally dissonant as an epistemological project, Global Asias encourages scholars to acknowledge the institutional designs and disciplinary practices that currently organize and make legible work on Asia and its diasporas while simultaneously highlighting the limits of, and points of noncontact between, the broader infrastructures (including area studies, ethnic studies, diaspora studies, and the disciplines and interdisciplines) under which such work has traditionally been organized. In addition to offering a conceptual topography of Global Asias, this essay proposes three praxis-oriented concepts—relational nonalignment, structural dissonance, and imaginable ageography—that enable Global Asias as a tactical and evolving approach to the study of Asia and its multiple diasporas, one which actively resists the drive toward “critical consolidation” that often results from academic paradigm work.